Laboratory measurements of the elastic and anelastic parameters of limestone at seismic frequencies - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (SEG, 2013)
A study of pore fluid effects on the elastic and anelastic properties of sedimentary rocks is important for seismic data interpretation and for monitoring the fluid movement during hydrocarbon extraction in producing fields. A significant portion of the world's hydrocarbon reserves are found in limestone reservoirs. An understanding of fluid effects on limestone properties is essential to characterize these reservoirs accurately. We present the results of low frequency (0.1 – 120 Hz) laboratory measurements of the elastic and anelastic properties of dry and water-saturated Savonnieres oolitic limestone (permeability – 3.2 mD, porosity – 29%) carried out at an effective pressure of 15 MPa which were complemented with indentation tests conducted under ambient conditions. Our measurements displayed reduction of the Young and shear moduli when changing from dry to water saturation conditions. The reduction of the Young modulus of the rock was also confirmed by the results of the indentation testing. The applicability of Gassmann's fluid substitution theory for the interpretation of obtained results was also tested during these experiments.